How Do Prospective Elementary and Gifted Education Teachers Perceive Scientists and Distinguish Science from Pseudoscience? - Sezen Camci-Erdogan (Journal of Education in Science, Environment and Health)
The present study aims to examine the perceptions towards scientists and science/pseudoscience distinctions of gifted education and elementary education teacher candidates who will educate gifted students especially at the elementary education level. A total of 92 volunteer prospective teachers, composed of candidates from gifted education and elementary education departments, participated in the study, which was carried out as a survey research. The data were collected using the Draw-a-Scientist Test and the Science/Pseudoscience Distinction Scale. The results of the study showed that both groups of prospective teachers‘ crafted drawings that reflected stereotypical perceptions in terms of appearance, work carried out by scientists, and gender. However, according to the results of the independent samples t-test, the elementary education teacher candidates were found to reflect more stereotypical characteristics in their drawings of scientists than the gifted education teacher candidates. The candidates‘ science/pseudoscience distinction scores did not significantly differ in department and there was a negative significant correlation between stereotypical image scores and scientific method scores.